Analisis Life Cycle Assessment (LCA) Pada Pengolahan Air Limbah di Pahu Makmur Palm Oil Mill: Life Cycle Assessment (LCA) Analysis of Wastewater Treatment at Pahu Makmur Palm Oil Mill - DWI ERMAWATI RAHAYU; EDHI SARWONO; M IBNU ALFARIDHO (Jurnal Teknologi Lingkungan, 2023)
ABSTRACT One of the potential wastes generated by the Crude Palm Oil (CPO) production process is Palm Oil Mill Effluent (POME). POME wastewater can produce Greenhouse Gases (GHG) and high levels of organic materials such as COD, BOD, and total nitrogen, which have impacts on the environment. This study aims to analyse the environmental impacts of POME wastewater treatment using the Life Cycle Assessment (LCA) method based on SNI ISO 14040:2016. The LCA analysis was aided by SimaPro v 9.3.0 software using the IMPACT 2002+ calculation method. The research focuses on measuring the environmental impacts of the POME waste treatment process in a 1 ton CPO production unit, with impact categories including global warming, water eutrophication, and respiratory organics. The research limitation is set to "gate to gate" due to the input being limited to the waste treatment process of the production plant. It was found that the environmental impacts generated are as follows: Global warming (8.47E+08 kg CO2eq/day) with contributions from biogenic CH4, N2O, fossil CH4, and fossil CO2 emissions; water eutrophication (33,622.8 kg PO4eq/day) with contributions from COD and total nitrogen emissions; and respiratory organics (253,197.7 kg C2H4eq/day) with contributions from biogenic CH4 emissions. In this case, the sludge pit process has the highest contribution to each impact category, accounting for 37.8%. The high percentage of contribution from the sludge pit to the impact category is known due to the biological process of organic matter decomposition, which generates methane biogas. Therefore, a recommended approach that can be implemented to manage POME waste sustainably is to construct an anaerobic digester to capture the released biogas and utilize it as an energy source for biogas power plants. This action is environmentally, economically, and socially viable.   ABSTRAK Salah satu potensi limbah yang dapat dihasilkan oleh Proses Produksi CPO adalah Palm Oil Mill Effluent (POME). Air limbah tersebut sangat berbahaya bagi lingkungan apabila tidak dikendalikan. Analisis ini bertujuan mengetahui kondisi eksisting dan evaluasi dampak lingkungan pada pengolahan air limbah POME serta memberikan rekomendasi yang dapat dilakukan oleh perusahaan sebagai bahan pertimbangan untuk perbaikan berkelanjutan. Dalam penelitian ini metode yang digunakan yaitu Life Cycle Assessement (LCA) berdasarkan SNI ISO 14040:2016. Batasan penelitian yang dilakukan dalam analisis LCA menggunakan batasan Gate to Gate yaitu hanya pada hilir kegiatan di IPAL Pahu Makmur Palm Oil Mill. Diperoleh bahwa sumber dampak lingkungan yang diakibatkan pada pengolahan limbah POME di IPAL PMPOM yaitu berasal dari enam unit kolam. Dampak lingkungan yang dihasilkan yaitu global warming dengan memperoleh nilai karakterisasi dampak sebesar 8,47E+08 kgCO2eq. Dampak ini dihasilkan dari kontribusi emisi dari CH4 biogenik, N2O, CH4 fosil dan CO2 Fosil. Dampak selanjutnya yaitu aquatic eutrophication dengan nilai karakterisasi dampak sebesar 33.622,8 kgPO4eq. Nilai tersebut dihasilkan dari dua kontribusi emisi yang bersumber dari parameter COD dan Total Nitrogen. Dampak selanjutnya respiratory organic dengan nilai karakterisasi dampak sebesar 253.197,7 kgC2H4eq. Rekomendasi yang dapat dilakukan oleh perusahaan untuk melakukan tindakan berkelanjutan yaitu dengan membuat digester anaerobik sebagai pemanfaatan Pembangkit Listrik Tenaga Biogas (PLTBg). Tindakan ini layak secara lingkungan, ekonomi dan sosial.